Use of a virtual 3D anterolateral thigh model in medical education: Augmentation and not replacement of traditional teaching?. Issue 2 (February 2020) - Lo, Steven; Abaker, Abdul Shakor Sandel; Quondamatteo, Fabio; Clancy, Jenny; Rea, Paul; Marriott, Michael; Chapman, Paul
Summary: There is a pressing need for simulated forms of medical, and in particular, anatomical learning. Current modalities of teaching are limited to either traditional 2-dimensional forms of learning, such as textbook, research papers and lectures, or more costly 3-dimensional modes including cadaveric dissection. Despite the overwhelmingly 3-dimensional nature of plastic surgery, virtual 3D models are limited. Here, we provide the first description of the development and utilisation of a virtual 3D flap model in medical education in the undergraduate curriculum. Methods and results: A 3D anterolateral (ALT) model was developed with close integration of specialists in simulation and visualisation, anatomists and clinicians, allowing 'virtual dissection' of the anatomy of the ALT flap. This was utilised in a B. Sc . Anatomy undergraduate course in 2017/18 and 2018/19. Student feedback noted an overwhelming preference for the 3D model (74%) as the first choice of educational methodology, versus lectures (26%), textbooks (0%) and research papers (0%) ( p = 0.0035). Extraneous cognitive load may be reduced with 3D models, with students rating these as easier to learn from than textbook or research papers ( p = 0.00014 and p < 0.00001, respectively). Notably, no statistically significant difference was found in the perceived ease of learning between 3D models and lectures. Conclusions: This study highlights a striking user preference for virtual 3D models as compared to for traditional teaching methods. Nonetheless, 3D models are likely to enhance rather than replace lectures, with this study suggesting that teaching by experts is likely to remain an essential part of medical education.